Beyond economic growth: the synergistic effects of globalization, environmental policies, and the triple green strategy on environmental sustainability in OECD countries - Ma, Xiang; Ben-Salha, Ousama; Choukaier, Dhouha (Frontiers in Environmental Science, 2025)
OECD countries, despite being global leaders in economic and technological advancements, face significant environmental challenges due to industrial expansion, resource depletion, and globalization. Achieving ecological sustainability requires a comprehensive strategy integrating green energy transition, financial incentives, technological diffusion, and stringent environmental policies. This study investigates the impact of the “Triple Green Strategy”—green energy (GE), green innovation (GI), and green finance (GF)—alongside ecological policies (EP), technological diffusion (TD), economic growth (EG), and globalization (GB) on environmental deterioration (ED) across 34 OECD countries from 1990 to 2022. Unlike prior research limited to single-factor analysis or narrow environmental indicators, this study adopts the ecological footprint as a comprehensive measure of environmental degradation and incorporates globalization and policy frameworks into an integrated model. Using two-step system GMM estimation, the analysis accounts for endogeneity, dynamics, and cross-sectional dependence, with additional robustness checks via FGLS, CCEMG, and FE models across three distinct periods: pre-crisis (1990–2007), post-crisis (2008–2019), and the pandemic era (2020–2022). The results show that GI consistently reduces ED in the pre-crisis phase (β = −0.007, p < 0.01), while EP becomes significant only before the financial crisis. TD and EG stand out as major contributors to environmental pressure, especially during the post-crisis and pandemic years. Interestingly, GE is found to have a positive link with ED during the pandemic period (β = 0.034, p < 0.01), which may reflect temporary inefficiencies in the transition toward cleaner energy. Granger causality analysis uncovers two-way relationships between ED and GF, EG, and TD, pointing to complex feedback mechanisms. Based on these findings, the study proposes policy actions aligned with SDG goals, including tailored recommendations on innovation funding, green financial tools, and regulatory measures. While the focus on OECD countries introduces some data and sample limitations, the study offers a detailed picture of how green policies interact with broader economic shifts and provides practical, adaptable guidance for advancing sustainability.